Mental Health Problems and Their Association With Internet Use in Medical Residents - Ueno, Tsukasa; Ito, Kazushi; Murai, Toshiya; Fujiwara, Hironobu (Frontiers in Public Health, 2020)
Objectives: Mental health problems (MHP) among medical residents are often found in clinical settings, and it sometimes leads to professional lapses. Evidence suggests that excessive Internet use (IU) is associated with MHP. We investigated residents' MHP assessing depression, anxiety, and self-esteem and their association with IU in a longitudinal design. Methods: A total of 208 residents participated in the study. The General Health Questionnaire (GHQ) and the Patient Health Questionnaire (PHQ) and Rosenberg Self-Esteem Scale (RSES) were used to assess anxiety, depression, and self-esteem. Generalized Problematic Internet Use Scale 2 (GPIUS2) was applied for IU assessment. The data were acquired twice, at baseline and three months later when the risk of MHP emergence is the highest during residency. Results: GHQ was higher among residents with MHP (Group M, N=36) than those without it (Group NM, N=172) at follow-up (T2). PHQ was higher and self-esteem was lower in Group M than Group NM at baseline (T1) and T2. GPIUS2 total and subscale “preference of online social communication (POSI)” scores were higher in Group M than Group NM. In correlational analyses, POSI at T2 was positively correlated with PHQ at T1 and T2, and negatively correlated with RSES at T2. Conclusions: Depression and self-esteem would predict IU at the timing when the risk of MHP emergence is the highest for residents, indicating potential risks for excessive IU or IU as a compensatory coping behaviour. IU might be an up-to-date index of mental health care for residents along with depression and self-esteem.